The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acsomega.2c04836
|View full text |Cite
|
Sign up to set email alerts
|

Growth Inhibition of Sulfate-Reducing Bacteria during Gas and Oil Production Using Novel Schiff Base Diquaternary Biocides: Synthesis, Antimicrobial, and Toxicological Assessment

Abstract: Upstream crude oil production equipment is always exposed to destruction damagingly which is caused by sulfate-reducing bacterium (SRB) activities that produce H 2 S gas, which leads to increased metal corrosion (bio-fouling) rates and inflicts effective infrastructure damage. Hence, oil and gas reservoirs must be injected with biocides and inhibitors which still offer the foremost protection against harmful microbial activity. However, because of the economic and environmental risks associated with biocides, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…The results showed that the nanocomposites exhibited good antifungal efficacy against both fungal strains. A wide and relatively heterogeneous inhibition zone was detected, which characterizes the antibacterial ring of fungal strains. The zones of inhibition for Corynespora cassiicola and Neoscytalidium dimidiatum correspond to 22.00 ± 0.52 mm and 18.00 ± 0.58 mm (Figure a,b). And, the extract is not antifungal against both Corynespora cassiicola and Neoscytalidium dimidiatum (Figure c,d).…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the nanocomposites exhibited good antifungal efficacy against both fungal strains. A wide and relatively heterogeneous inhibition zone was detected, which characterizes the antibacterial ring of fungal strains. The zones of inhibition for Corynespora cassiicola and Neoscytalidium dimidiatum correspond to 22.00 ± 0.52 mm and 18.00 ± 0.58 mm (Figure a,b). And, the extract is not antifungal against both Corynespora cassiicola and Neoscytalidium dimidiatum (Figure c,d).…”
Section: Resultsmentioning
confidence: 99%
“…7 Traditionally, the alloying method has been used for alleviating the SRB-induced MIC around the world over the past few years, the antibacterial elements have been incorporated into the metals to improve their performance; however, the antibacterial and corrosion resistances of these alloys are often unsatisfactory because the incorporated elements are usually limited by their solid solubility in the alloy matrix. 8 Moreover, excessive incorporation amounts of the alloy elements also have a negative influence on their mechanical properties. 9 Recently, the application of active substances, such as corrosion inhibitors and bactericides, has become an efficient and convenient approach for suppressing MIC induced by SRB.…”
Section: Introductionmentioning
confidence: 99%